Thet Freske Riim Tractatus Alvini - Campbell, A. author. aut Link
VIII, 234 p. 2 illus.
Keywords: This edition of Thet Freske Riim and the expanded Dutch version of it known as the Tractatus Alvini was begun in 1940 and gradually completed over a period of eleven years. It is hoped that the texts presented will be found to be sufficiently "diplomatic", yet at the same time readable. A complete Glossary to the Riim is provided, and the linguistic study therefore aims merely at placing before the reader the broad features of its language, for the fulness of the Glossary will enable a scholar to obtain with ease and rapidity all the material that the text offers on any point of phonology, accidence, orthography or syntax. The Glossary is supplemented by brief Interpretative Notes, in which difficulties are discussed, and in which obvious scribal errors are corrected for the convenience of those wishing to read the text rapidly. The late Middle Dutch of the Tractatus Alvini has not been thought to require any linguistic commentary. In sections B, C and D of the Introduction, and in the Explanatory Notes, the subject-matter is thoroughly examined. It may not be irrelevant to point out here that two pejorative judgments upon the Riim must be reconsidered in the light of my work. Firstly, its subject-matter has been called "fantastic" 1.